2012
DOI: 10.1002/adfm.201102544
|View full text |Cite
|
Sign up to set email alerts
|

Novel Platinum–Cobalt Alloy Nanoparticles Dispersed on Nitrogen‐Doped Graphene as a Cathode Electrocatalyst for PEMFC Applications

Abstract: A novel synthesis procedure is devised to obtain nitrogen‐doping in hydrogen‐exfoliated graphene (HEG) sheets. An anionic polyelectrolyte–conducting polymer duo is used to form a uniform coating of the polymer over graphene sheets. Pyrolysis of graphene coated with polypyrrole, a nitrogen‐containing polymer, in an inert environment leads to the incorporation of nitrogen atoms in the graphene network with simultaneous removal of the polymer. These nitrogen‐doped graphene (N‐HEG) sheets are used as catalyst supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
149
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(162 citation statements)
references
References 38 publications
8
149
1
4
Order By: Relevance
“…Improved electrocatalytict activity was observed due to the small size, uniform dispersion and a high electrochemical active surface area of the nanocomposites. Recently, more studies on NG-or N-rGO-supported Pt electrocatalysts have also been reported; all these results demonstrate the significant function of N doping in producing highly efficient ORR electrocatalysts [128][129][130].…”
Section: Ng As Support Materials For Orrmentioning
confidence: 91%
“…Improved electrocatalytict activity was observed due to the small size, uniform dispersion and a high electrochemical active surface area of the nanocomposites. Recently, more studies on NG-or N-rGO-supported Pt electrocatalysts have also been reported; all these results demonstrate the significant function of N doping in producing highly efficient ORR electrocatalysts [128][129][130].…”
Section: Ng As Support Materials For Orrmentioning
confidence: 91%
“…Chemical modification of the graphene lattice by heteroatom doping is a common way to form anchor sites in graphene. The N-doping of graphene supports can reportedly increase the dispersion of Pt catalysts [15] and prevent Pt agglomeration [16,17]. This improves the catalyst durability and efficiency for the ORR, compared with that of pristine graphene supports.…”
Section: Introductionmentioning
confidence: 99%
“…Various potential cathode catalysts such as Pt-M (M = Fe, Co, Ni, etc.) alloy catalysts, [12][13][14][15][16][17][18][19][20][21][22][23] Pt core-shell catalysts, 24,25 and Ptfree catalysts 26,27 have been investigated by many research groups. Among these, Pt alloy catalysts were found to exhibit better ORR activities than Pt in acidic solutions.…”
Section: Introductionmentioning
confidence: 99%